2009
DOI: 10.1096/fj.09-133215
|View full text |Cite
|
Sign up to set email alerts
|

A novel domain in histone deacetylase 1 and 2 mediates repression of cartilage‐specific genes in human chondrocytes

Abstract: The role of histone deacetylase 1 and 2 (HDAC1 and HDAC2) in regulating cartilage-specific gene expression was explored in primary human chondrocytes. HDAC1 and HDAC2 protein levels were elevated in chondrocytes from osteoarthritic patients, consistent with a down-regulation of some cartilage marker genes. When expressed in these cells, HDAC1 and HDAC2 repressed aggrecan and collagen 2(alpha1) expression but differed in their repression of collagen 9(alpha1), collagen 11(alpha1), dermatopontin, and cartilage o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
102
0
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 97 publications
(103 citation statements)
references
References 41 publications
0
102
0
1
Order By: Relevance
“…27 The expression of HDAC4 was increased in OA chondrocytes, whereas knockdown of HDAC4 attenuated the induction of catabolic gene expression in chondrocytes. 28 In another study, direct correlation was observed in the enhanced expression of MMP-13 and increased HDAC7 levels in OA cartilage.…”
Section: Discussionmentioning
confidence: 93%
“…27 The expression of HDAC4 was increased in OA chondrocytes, whereas knockdown of HDAC4 attenuated the induction of catabolic gene expression in chondrocytes. 28 In another study, direct correlation was observed in the enhanced expression of MMP-13 and increased HDAC7 levels in OA cartilage.…”
Section: Discussionmentioning
confidence: 93%
“…Chromatin modifications are one of the molecular mechanisms that mediate epigenetic regulation (43). Of them, HDACs, the chromatin-modifying enzymes, remove the acetyl groups, leading to chromatin condensation and repres- sion of transcription (44). A HDAC inhibitor also is involved in the expression of several genes.…”
Section: Results Of Immunostainingmentioning
confidence: 99%
“…Moreover, inhibition of histone deacetylases (HDACs) stimulates expression of SOX9-activated cartilage ECM genes and induces histone acetylation in the region of the Col2a1 enhancer in primary chondrocyte cultures (Furumatsu et al 2005). Overexpression of HDAC1 or 2 in chondrocytes results in down-regulation of expression of Aggrecan and Col2a1, providing further evidence for epigenetic control of this aspect of chondrocyte function (Hong et al 2009). …”
Section: Extracellular Matrixmentioning
confidence: 90%